Integral Ukrainian nationalism in the comparative context - Dwojnych, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents main analytic problems that Victor Polishchuk tackles in his book "Ideologia nacjonalizmu ukraińskiego" [The Ideology of Ukrainian Nationalism]. Key features of integral Ukrainian nationalism in Dontsov`s version have been presented here on the background of the nationalisms of two neighbouring countries, Germany and Poland, in order to identify the similarities and differences between them in the realm of axiological systems.
Keywords: nationalism; Dontsov; ethics; ideology